Fiscal Policy and External Shocks in Nigeria - Ologbenla, Patrick (Journal of Economics and Behavioral Studies, 2019)
The study assessed the effects of external shocks on fiscal policy in Nigeria. Vector auto-regression VAR estimating technique is adopted to achieve the set objectives of the study. The VAR model comprises of the following variables GDP, oil output, oil price, government revenue, government expenditure, external reserve, exchange rate, fiscal balance, and non-oil export. These variables represent the external shocks, the growth variables, fiscal variables and some other macroeconomic variables. The VAR results show that oil price and non-oil export are the most important external shocks affecting fiscal policy in Nigeria. It was also discovered that public debt shock has no significant impact on government expenditure. In addition, external reserve and exchange rate shocks also have a significant impact on fiscal policy. Finally, government expenditure shock failed to have a significant impact on the GDP. The implication of these results is that the effectiveness of fiscal policy in achieving macroeconomic objectives in Nigeria depends on these identified shocks.